2022
DOI: 10.3390/ma15186337
|View full text |Cite
|
Sign up to set email alerts
|

A Fukui Analysis of an Arginine-Modified Carbon Surface for the Electrochemical Sensing of Dopamine

Abstract: Amino acid-modified carbon interfaces have huge applications in developing electrochemical sensing applications. Earlier reports suggested that the amine group of amino acids acted as an oxidation center at the amino acid-modified electrode interface. It was interesting to locate the oxidation centers of amino acids in the presence of guanidine. In the present work, we modeled the arginine-modified carbon interface and utilized frontier molecular orbitals and analytical Fukui functions based on the first princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The review identified that rather than the native graphene/fullerene nanomaterial, the polymer nanocomposite-integrated graphene/fullerenes were more suitable for hydrogen storage purposes. Polymer nanocomposites involving a combination of two or more entities invariably hold an added advantage of being able to overcome the limitations of the individual entities [ 176 ]. The potentials and possibilities from these nanocomposites were highlighted and the need to expand has been emphasized.…”
Section: Future Recommendations and Conclusionmentioning
confidence: 99%
“…The review identified that rather than the native graphene/fullerene nanomaterial, the polymer nanocomposite-integrated graphene/fullerenes were more suitable for hydrogen storage purposes. Polymer nanocomposites involving a combination of two or more entities invariably hold an added advantage of being able to overcome the limitations of the individual entities [ 176 ]. The potentials and possibilities from these nanocomposites were highlighted and the need to expand has been emphasized.…”
Section: Future Recommendations and Conclusionmentioning
confidence: 99%
“…Electroanalytical techniques should have attributes, such as quick response time, simplicity of use, cost-effectiveness, high sensitivity, selectivity for the determination of ABZ in different matrices, suitability for miniaturization, and portability, thus, enabling on-site monitoring [ 23 ]. In recent years, solid and modified electrodes were commonly used in electroanalytical measurement due to their ability in detecting drugs prone to undergoing oxidation reactions [ 24 ]. By taking measurements using cyclic voltammetry (CV), modified electrode sensitivity is kept track of.…”
Section: Introductionmentioning
confidence: 99%
“…By taking measurements using cyclic voltammetry (CV), modified electrode sensitivity is kept track of. To perform the CV experiment, the choice of the working electrode is crucial [ 24 ]. Due to environmental concerns and EU regulations restricting the utilization and storage of mercury [ 25 ], the use of metallic (e.g., gold, platinum, silver, palladium, and indium tin oxide) and carbon-based (e.g., glassy carbon, carbon paste, boron doped diamond, and graphite) substrates has increased.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical reduction is connected to the modified MPEG resistance value, and the peeling method was used for the plasma-assisted electrochemical exfoliated system [ 21 ]. Another research field of molecular computing, such as the Fukui function application, and modified and exfoliated graphene, could help the degree of electronic transition on the surface of graphene, which is widely used in biochemical medicine [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%